Minimally invasive treatment of complex collections: safety and efficacy of recombinant tissue plasminogen activator as an adjuvant to percutaneous drainage - Falsarella,Priscila Mina (2018)
Abstract Objective: To analyze the efficacy of recombinant tissue plasminogen activator (r-TPA) injection in the evolution of percutaneous drainage of thick collections. Materials and Methods: This was a single-center study involving the retrospective analysis of hospitalized patients undergoing percutaneous drainage of thick (superficial or intracavitary) fluid collections, followed by injection of a fibrinolytic agent (r-TPA) into the affected space. Results: A total of 53 percutaneous drainage procedures, with r-TPA injection, were performed in 51 patients. Abdominal and pelvic collections were the most common, being seen in 38 (73%) of the procedures; in 35 (66%), the etiology of the collection was attributed to postoperative complications. A total of 61 catheters were used in order to drain the 53 collections. Of those 61 catheters, 52 (85%) were large (12-16 Fr) and 9 (15%) were small (4-10 Fr). The mean r-TPA dose was 5.7 mg/collection per day, and the mean time from r-TPA injection to drain removal was 7.7 days. Percutaneous drainage in combination with r-TPA injection was successful in 96% of the cases. None of the patients showed coagulation changes during the study period. Conclusion: The use of once-daily, low-dose r-TPA for up to three consecutive days, as an adjunct to percutaneous drainage of thick collections, with or without loculation, appears to be an effective technique.